Cooperative localization and navigation theory, research, and practice - Gao, Chao, 1985-; Zhao, Guorong (Engineering professor); Fourati, Hassen (Boca Raton : Taylor & Francis, CRC Press, 2019)
This book captures the latest results and techniques for cooperative localization and navigation drawn from a broad array of disciplines. It provides the reader with a generic and comprehensive view of modeling, strategies, and state estimation methodologies in that fields. It discusses the most recent research and novel advances in that direction, exploring the design of algorithms and architectures, benefits, and challenging aspects, as well as a potential broad array of disciplines, including wireless communication, indoor localization, robotics, emergency rescue, motion analysis, etc.
OCLC-licensed vendor bibliographic record.
Keywords: Cooperative localization; Electronics in navigation; TECHNOLOGY / Electricity